Os ciclos orbitais (Ciclos de Milankovitch) e as mudanças climáticas: uma proposta interdisciplinar para a Educação Básica - Xavier, Clailton de Oliveira (2021)
A deeper study of Astronomy in elementary education is of great relevance in order to increase the quality of the discussions in the classroom. In particular, the investigation of the Milankovitch Cycles (Orbital Cycles) and its relationship with the long-term climate changes of the planet should foster questions about the characteristics of the precession movement, the ecliptic obliquity, and the variation of the eccentricity of the Earth's revolution movement around the Sun. In addition to clarifying the occurrence of the cyclical events of nature as the glaciations. An interdisciplinary and multi-referential approach was used, in order to characterize a complex view of the reality to be studied. This paper proposes a continuing training workshop in Astronomy for elementary education teachers, where the possible relationship between the Earth's Orbital Cycles and the long-term climate changes of the planet. Exploratory research was conducted with a qualitative approach, in which a diagnosis was initially conducted. It was observed the formation and the difficulties of the teachers of the State College Paulo VI related to the teaching of Astronomy in elementary education; An Astronomy knowledge test was applied to verify the actual situation of the teachers of the night shift, evaluating the needed knowledge for the teaching of Astronomy. As an educational product, two didactic sequences were organized with scripts and classes in digital format, guiding the application of the contents used in the classroom for the teachers of the subjects that work with astronomical knowledge.